Phytomediated synthesis of silver nanoparticles against microbial pathogens and cytotoxicity on human breast cancer cells (MCF-7); Resource-Efficient Technologies; No 1 - Karthiga P.; Shankar T.; Karthick K.; Swarnalatha K. (2020, 2020)
Title screen